Take the Short Route: Equilibrium Default and Debt Maturity - Aguiar, Mark; Amador, Manuel; Hopenhayn, Hugo; Werning, Iván (Econometrica, 2019)
We study the interactions between sovereign debt default and maturity choice in a setting with limited commitment for repayment as well as future debt issuances. Our main finding is that, under a wide range of conditions, the sovereign should, as long as default is not preferable, remain passive in long‐term bond markets, making payments and retiring long‐term bonds as they mature but never actively issuing or buying back such bonds. The only active debt‐management margin is the short‐term bond market. We show that any attempt to manipulate the existing maturity profile of outstanding long‐term bonds generates losses, as bond prices move against the sovereign. Our results hold regardless of the shape of the yield curve. The yield curve captures the average costs of financing at different maturities but is misleading regarding the marginal costs.